Overprotective Parenting and Its Challenges for Character Development Among Students in the Modern Era: A Literature Review - Mochammad Yoyok Adianto; Nanang Kosim; Muhammad Riyadi; Benny Prasetiya (PT. Education Research Center, 2026)
This study examines the phenomenon of overprotective parenting and its implications for students' character development in the modern era through a literature review. The study is motivated by the increasing tendency of parents to provide excessive protection due to concerns about children's safety, academic achievement, and future success. Using a qualitative approach with library research, this study synthesizes recent empirical findings and theoretical perspectives on overprotective parenting, helicopter parenting, and character education. The analysis reveals that overprotective parenting is characterized by excessive parental control, intensive intervention, restricted autonomy, and dominance in children's decision-making processes. Although intended to protect children, such parenting practices may inhibit the development of essential character traits, including independence, responsibility, resilience, decision-making ability, and social competence. The study further identifies several contributing factors to overprotective parenting, including parental anxiety, perceptions of environmental threats, social pressure, digital media influence, and uncertainty in modern society. To address these challenges, the study proposes balanced parenting, guided autonomy, responsibility-based learning, parent–teacher collaboration, and parenting literacy as strategies to strengthen students' character. The findings contribute to the literature on parenting and character education by emphasizing the importance of balancing parental protection with children's opportunities to develop autonomy and resilience.